Efektivitas Online Multimedia Edukasi Berbasis Whatsapp Terhadap Koping Pada Pasien Kanker Stadium Lanjut - Riga Opri Sandrelly; Nurul Huda; Erika Erika; Sri Wahyuni; Reni Zulfitri (Jurnal Ners, 2025)
Advanced cancer patients have more complex problems. Education is one approach to support the care of advanced cancer patients. In the digital era, communication technology such as WhatsApp can be utilized as an effective means of education, given its ability to be accessed by various groups. The purpose of this study was to determine the effectiveness of WhatsApp-based online multimedia education on coping in advanced cancer patients. This study used a quasi-experimental design with a non-equivalent control group research design. Sampling this study using purposive sampling with a total of 66 people consisting of 33 interventions and 33 controls. The intervention group received a WhatsApp-based educational intervention in the form of a module and was equipped with a telephone call from the researchers for follow-up conducted for 10 days. The measuring instrument used in this study was the Brief Cope questionnaire to measure coping. This study used dependent t-test as data analysis. Result showed a significant difference in mean coping PFC and EFC before and after intervention (p value = <0.001) in the experimental group, while for the control group there was no significant difference in the mean coping of PFC (p value = 0.317) and EFC (p value = 0.305). This study suggests that WhatsApp-based education can enhance coping in patients with advanced cancer. The importance of developing educational materials tailored to the needs of advanced cancer patients.